PENGGUNAAN GENERATOR HHO PADA SEPEDA MOTOR DENGAN MENGGUNAKAN SISTEM BI-FUEL DENGAN VARIASI LARUTAN ELEKTROLIT - Anggun Angkasa Bela Persada; Ika Kusuma N; M. Khairul Abrar (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Transport is one of the main community needs, but along with the increasing number of transport such as motorcycles and increasing also use of fuel oil.While fuel oil are currently derived from fossil where is not sustainable, alternative fuel can use water as fuel, by the process elektrolysis. Water is a compound composed of hydrogen and oxygen, both compound this is a flammable that can be used as alternative fuel or known as gas HHO . When used alternative fuel, gas HHO used along with fuel oil (bi-fuel) .This research discussed of the use of a generator HHO (tool gas producer HHO) on a motorcycle to a variation with an electrolyte namely fresh water, sea water and aquadesh in order to know some of the form a generator HHO that is the generator, the rate of the production of gas and efficiency of gas. This research obtained the best grades HHO power generator at 6.01 watts , the rate of the production of gas by 0.015 and efficiency as much as 1,265 when using aquades. Keywords: HHO, HHO generator, electrolysis